Synthesis of coral-like silver chloride-polypyrrole nanocomposites derived from silver nanoparticles and the study of their structural, thermal, optical and electrical properties - Kanwal, Farah; Batool, Aisha; Aslam, Muniba; Aziz, Fatima; Shahzad Ahmad (Kuwait Journal of Science, 2021)
In this research, we develop a facile method for the synthesis of AgCl:PPy nanocomposites with enhanced structural, thermal, optical and conducting properties.Polypyrrole monomer was in-situ doped with varied weight percentages of as-synthesized Ag nanoparticles by following simple chemical oxidation polymerization technique to form AgCl:PPy nanocomposites. The AgCl nanostructures with tree-like coral morphology distributed uniformily into the PPy matrix without any segregation. The fourier transform infrared spectroscopy results reveal the successful incorporation of AgCl in the organic structure of PPy. X-ray diffraction analysis shows that the formation of AgCl nanostructures in PPy matrix during chemical polymerization process that increases the crystallinity of amorphous PPy. The TGA analysis demonstrates the improved thermal stability of PPy nanocomposites due to developed physiochemical interactions between the AgCl and PPy moities, also inferred from fourier transform infrared results. It is noted that electrical conductivity of AgCl:PPy nanocomposites is significantly controlled by the weight percentage of dispersed Ag nanoparticles in the polymerization assembly. Highest conductivity (1335 S cm-1) of PPy nanocomposite is attributed to the decrease in particle size, shortening of the PPy chain lenght and lower band gap energy presented at critical weight percentage of Ag nanoparticles.